Perspectives on a US–Mexico Border Community’s Diabetes and “Health-Care” Access Mobilization Efforts and Comparative Analysis of Community Health Needs over 12 Years - Rosales, Cecilia Ballesteros; de Zapien, Jill Eileen Guernsey; Chang, Jean; Ingram, Maia; Fernandez, Maria L.; Carvajal, Scott C.; Staten, Lisa K (Frontiers in Public Health, 2017)
This paper describes a community coalition–university partnership to address health needs in an underserved US–Mexico border, community. For approximately 15 years, this coalition engaged in community-based participatory research with community organizations, state/local health departments, and the state’s only accredited college of public health. Notable efforts include the systematic collection of health-relevant data 12 years apart and data that spawned numerous health promotion activities. The latter includes specific evidence-based chronic disease-preventive interventions, including one that is now disseminated and replicated in Latino communities in the US and Mexico, and policy-level changes. Survey data to evaluate changes in a range of health problems and needs, with a specific focus on those related to diabetes and access to health-care issues—identified early on in the coalition as critical health problems affecting the community—are presented. Next steps for this community and lessons learned that may be applicable to other communities are discussed.